2009
DOI: 10.1111/j.1755-0238.2009.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of 11 phenolic acids and five flavan-3-ols in cv. Vidal: impact of natural icewine making versus concentration technology

Abstract: Background and Aims:In an effort to protect the development of the icewine production industry, this study aimed to find indicators to distinguish between authentic and non-authentic icewines. Methods and Results: Fully ripened berries were used to prepare three types of high-sugar grape juices: naturally frozen juice, refrigerator-frozen juice and concentrated juice. The content of phenolic acids and flavan-3-ols in the samples before and after fermentation was assayed. Significant differences were found in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In wines, the phenolic acid content was higher than that found in grapes (Table 6), possibly caused by a contribution of phenolic acids presented in the pulp (Tian et al. 2009).…”
Section: Discussionmentioning
confidence: 79%
“…In wines, the phenolic acid content was higher than that found in grapes (Table 6), possibly caused by a contribution of phenolic acids presented in the pulp (Tian et al. 2009).…”
Section: Discussionmentioning
confidence: 79%
“…Wines belonging to this cluster presented lower values of hydroxybenzoic acids, so the extraction and concentration of these compounds by freezing have been lower than in the cases of wines of the other two clusters. This fact may also be due to other factors such as variety (white versus red) and grape pressing (diffusion of phenolic compounds from the skin and seeds to the pulp).The presence and concentration of phenolic acids, flavan-3-ols and flavonols could differentiate between methods of artificial and natural icewines, as other authors revealed in Vidal variety (Tian et al, 2009b).…”
Section: Concentrações De Compostos Fenólicos (Mg/l) Em Amostras De Vmentioning
confidence: 92%
“…Most studies have focused on the winemaking technology, the extraction approaches of aromatic compounds and the impact of commercial yeasts on the production of aromatic compounds. [3][4][5][6] Very few studies have focused on the selection of indigenous icewine yeasts for its production. As far as we know, all Chinese icewines are fermented with international commercial S. cerevisiae strains.…”
Section: Introductionmentioning
confidence: 99%